Developing the Chemical Equilibrium-Scientific Habits of Mind Scale: Validity and Reliability Analysis - Pratama, Faiz Ilham; Amalia, Puspita; Rohaeti, Eli; Laksono, Endang Widjajanti (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
One of the challenges of the 21st century disruption era is the fast development of science and technology which was initiated by the hard work of scientists who have habits of mind. Habits of mind can be deepened into scientific habits of mind (SHOM) and can be encouraged to be used by students at the high school level. This research aims to develop and validate the SHOM questionnaire in chemical equilibrium. Modified 4D becomes an adapted development model. The questionnaire developed has 25 statement items originating from seven aspects of SHOM. Content validity was calculated using the Aiken V equation and involved seven expert judgments with 4 categories of answer choices and produced an average of 0.90, so the questionnaire tested content validity. Construct validity was calculated using the Pearson correlation coefficient involving 300 respondents from 7 public high schools and produced a mean of 0.581 which was above the r table (r table value = 0.113), thus meeting the construct validity criteria. The reliability of the questionnaire was calculated using Cronbach Alpha and got a mean score of 0.915 and the reliability was included in the very high category. Based on these findings, the SHOM questionnaire developed can be declared suitable for measuring SHOM for high school students.